An integrated genomic approach for the study of mandibular prognathism in the European seabass (Dicentrarchus labrax) - Babbucci, Massimiliano (Sci Rep, 2016)
Skeletal anomalies in farmed fish are a relevant issue affecting animal welfare and health and causing significant economic losses. Here, a high-density genetic map of European seabass for QTL mapping of jaw deformity was constructed and a genome-wide association study (GWAS) was carried out on a total of 298 juveniles, 148 of which belonged to four full-sib families. Out of 298 fish, 107 were affected by mandibular prognathism (MP). Three significant QTLs and two candidate SNPs associated with MP were identified. The two GWAS candidate markers were located on ChrX and Chr17, both in close proximity with the peaks of the two most significant QTLs. Notably, the SNP marker on Chr17 was positioned within the Sobp gene coding region, which plays a pivotal role in craniofacial development. The analysis of differentially expressed genes in jaw-deformed animals highlighted the “nervous system development” as a crucial pathway in MP. In particular, Zic2, a key gene for craniofacial morphogenesis in model species, was significantly down-regulated in MP-affected animals. Gene expression data revealed also a significant down-regulation of Sobp in deformed larvae. Our analyses, integrating transcriptomic and GWA methods, provide evidence for putative mechanisms underlying seabass jaw deformity.